1995
DOI: 10.1029/95jd00988
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric aerosol effective radius, surface area and volume estimated from infrared measurements

Abstract: A technique is presented for estimating the effective radius, surface area density, and volume density of stratospheric aerosols from infrared emission measurements. These parameters are required to assess the perturbation of the climate and chemical balance of the stratosphere following the largest volcanic eruption so far this century: that of Mount Pinatubo in the Philippines. The method uses a relationship between the surface area density and the volume density derived from balloon‐borne measurements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 42 publications
6
55
0
Order By: Relevance
“…In S1, equilibrium values of the aerosol surface area density (SAD) of (20.7 µm 2 cm −3 ) and of the size distributions effective radius (R eff ) of 0.35 µm (Figure 1(b)) are in the order of values observed in the northern hemisphere mid-latitudes in the stratosphere during the first year after the Mt Pinatubo eruption (Grainger et al, 1995;Bauman et al, 2003) but are approximately only half the size of observed values in the tropical stratosphere (SPARC, 2006). Clear but rather weak oscillations in the evolution of R eff in scenario 1 provide an indication that the aerosol population is balanced not until year 3 of integration.…”
Section: Aerosol Growthmentioning
confidence: 92%
“…In S1, equilibrium values of the aerosol surface area density (SAD) of (20.7 µm 2 cm −3 ) and of the size distributions effective radius (R eff ) of 0.35 µm (Figure 1(b)) are in the order of values observed in the northern hemisphere mid-latitudes in the stratosphere during the first year after the Mt Pinatubo eruption (Grainger et al, 1995;Bauman et al, 2003) but are approximately only half the size of observed values in the tropical stratosphere (SPARC, 2006). Clear but rather weak oscillations in the evolution of R eff in scenario 1 provide an indication that the aerosol population is balanced not until year 3 of integration.…”
Section: Aerosol Growthmentioning
confidence: 92%
“…Grainger et al, 1995). Although negatively biased to the SAGE II climatologies of Bauman et al (2003a, b) and Wurl et al (2010) as well as in situ observations of the balloonborne optical particle counter of the University Of Wyoming (Deshler et al, 2003), in the control experiment without a QBO, the model-predicted R eff lies within the uncertainty range of the measurements (HOM11).…”
Section: Effective Radiusmentioning
confidence: 94%
“…The explicitly calculated effective radius (ULAQ-CCM) or indirectly derived 15 using the Grainger et al (1995) method (GEOS-Chem) are both consistent with the SAGE-II derived estimates approximately one year after the Pinatubo eruption, with comparable integrated stratospheric sulfate mass (Pitari et al (2014); Visioni et al (2017b)). The breakdown of global SO x deposition fluxes, among SO 2 , SO 4 dry and wet deposition terms, is summarized in Table 4 for the two models, and a comparison is made with multimodel data presented in Lamarque et al (2013).…”
mentioning
confidence: 49%